Astrology and Cosmology in Early China : Conforming Earth to Heaven / [electronic resource] - Pankenier, David W. (Cambridge : Cambridge University Press, 2013)
The ancient Chinese were profoundly influenced by the Sun, Moon and stars, making persistent efforts to mirror astral phenomena in shaping their civilization. In this pioneering text, David W. Pankenier introduces readers to a seriously understudied field, illustrating how astronomy shaped the culture of China from the very beginning and how it influenced areas as disparate as art, architecture, calendrical science, myth, technology, and political and military decision-making. As elsewhere in the ancient world, there was no positive distinction between astronomy and astrology in ancient China, and so astrology, or more precisely, astral omenology, is a principal focus of the book. Drawing on a broad range of sources, including archaeological discoveries, classical texts, inscriptions and paleography, this thought-provoking book documents the role of astronomical phenomena in the development of the 'Celestial Empire' from the late Neolithic through the late imperial period.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Astrology, Chinese; Cosmology, Chinese